A lithium ion battery negative electrode dispersant and its preparation method and application
By grafting sulfonic acid functional groups on the negative electrode auxiliary material of lithium-ion battery to prepare modified carboxymethylcellulose sodium, the concentration polarization and lithium evolution problems caused by slow diffusion speed during fast charging and discharge of lithium-ion batteries are solved, and the battery performance and safety improvement are achieved.
Patent Information
- Application Number
- CN202210711082.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-06-22
AI Technical Summary
During the rapid charging and discharging process, traditional lithium-ion batteries have slow diffusion speed, which leads to concentration polarization and lithium-ion problems, which affects the cycle stability and safety of the battery.
By grafting functional groups that accelerate lithium ion conduction on the negative electrode auxiliary material sodium carboxymethylcellulose, the specific method is to prepare modified carboxymethylcellulose as the negative electrode dispersant by amide condensation reaction between sodium carboxymethylcellulose and sulfonic acid compound.
This technical method effectively accelerates the migration rate of lithium ions, improves the rate performance and cycling efficiency of the battery, reduces internal resistance, and improves the safety of the battery and the charging and discharging platform.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a negative electrode dispersant for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] The rapid development of new electronic devices and electric vehicles requires future rechargeable batteries to have high power, high energy density and fast charging performance. In rechargeable battery systems, ion transport is a key control step because it is much slower than electron transport in kinetics, and the transport speed of lithium ions has an important impact on the performance of the battery.
[0003] The diffusion of lithium ions in the negative electrode material is an important parameter that determines the charge and discharge rate of lithium-ion batteries. During rapid charge and discharge, the slow diffusion of Li+ will cause severe concentration polarization, resulting in a huge voltage drop at the negative electrode. When the negative electrode voltage is lower than 0V (vs. Li / Li+), lithium deposition will inevitably occur. The diffusion rate of lithium ions in traditional graphite is relatively low, and the lithium insertion potential of graphite is close to the reduction potential of lithium ions, which makes graphite easy to deposit lithium during rapid charging. Therefore, the development and application of materials with high lithium ion diffusion rates will help achieve rapid battery charging performance.
[0004] Chinese patent CN113045777A discloses a negative electrode dispersant and a lithium-ion battery containing the dispersant. Conventional sodium carboxymethyl cellulose contains abundant hydroxyl groups and a small amount of carboxyl groups. The hydroxyl groups on sodium carboxymethyl cellulose react with some bifunctional organic substances to make the linear sodium carboxymethyl cellulose into a sodium carboxymethyl cellulose with a three-dimensional network structure, thereby increasing its viscosity in water. However, the increase in molecular weight leads to a decrease in the solubility of sodium carboxymethyl cellulose, prolongs the gel preparation time, and increases the number of insoluble particles in the gel, resulting in an increase in impurities in the slurry, which is not conducive to the cycle stability during the battery charge and discharge process, and there is a risk of lithium precipitation. Summary of the invention
[0005] In view of this, in order to solve the above problems, the present invention provides a lithium ion battery dispersant and a preparation method and application thereof, and proposes grafting a functional group having the function of accelerating the conduction of lithium ions onto the negative electrode auxiliary material sodium carboxymethyl cellulose for preparing lithium ion battery pole pieces, accelerating lithium ion conduction and increasing battery capacity.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] <First aspect>
[0008] The invention provides a negative electrode dispersant for lithium ion batteries. The negative electrode dispersant for lithium ion batteries is a modified sodium carboxymethyl cellulose prepared by grafting a carboxyl group on sodium carboxymethyl cellulose and an amino group on a sulfonic acid compound through an amide condensation reaction.
[0009] The sulfonic acid compound is selected from one or more of alkanes, aromatics and heterocyclic compounds having amino and sulfonic acid functional groups.
[0010] Furthermore, the sulfonic acid compound is selected from one of lithium aminobenzenesulfonate, lithium m-aminobenzenesulfonate, lithium 2-amino-3,5-dimethylbenzenesulfonate, lithium methacrylate sulfonate, lithium allyl sulfonate, and lithium chloroethyl sulfonate.
[0011] <Second Aspect>
[0012] The present invention provides a method for preparing a negative electrode dispersant for a lithium ion battery, comprising the following steps:
[0013] S1, dissolving sodium carboxymethylcellulose powder in a strong acid solution, and obtaining carboxymethylcellulose acid after centrifugation;
[0014] S2, adding the sulfonic acid compound and the catalyst to a mixture of a hydrophilic organic solvent and water;
[0015] S3, adding the carboxymethyl cellulose acid of step S1 to the solution of step S2, heating for reaction, and drying the reaction product to obtain modified sodium carboxymethyl cellulose, wherein the heating temperature is 20-60°C, and the drying temperature is 40-150°C.
[0016] The volume ratio of the water to the hydrophilic organic solvent is 1 mL:2 mL to 1 mL:9 mL.
[0017] The hydrophilic organic solvent may be ethanol.
[0018] In step S2, the catalyst is selected from a salt condensation agent or a carbodiimide condensation agent used for amide condensation reaction.
[0019] The salt condensing agent is selected from one or more of O-(7-azabenzotriazole-1-yl)-bis(dimethylamino)carbonium hexafluorophosphate (HATU), O-(benzotriazole-1-yl)-bis(dimethylamino)carbonium hexafluorophosphate (HBTU), O-(5-chlorobenzotriazole-1-yl)-bis(dimethylamino)carbonium hexafluorophosphate (HCTU), O-(benzotriazole-1-yl)-bis(dimethylamino)carbonium tetrafluoroborate (TBTU), O-(N-succinimidyl)-bis(dimethylamino)carbonium tetrafluoroborate (TSTU), and O-(N-endo-5-norbornene-2,3-dicarbonimide)-bis(dimethylamino)carbonium tetrafluoroborate (TNTU).
[0020] The carbodiimide condensing agent is selected from one or more of dicyclohexylcarbodiimide (DCC), diisopropylcarbodiimide (DIC) and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDCI).
[0021] The weight ratio of sodium carboxymethyl cellulose, sulfonic acid compound and catalyst is 100 parts: 10-30 parts: 0.1-5 parts. The present invention further found that sodium carboxymethyl cellulose and sulfonic acid compound can only prepare a dispersant with good performance within a suitable ratio range. When the amount of sulfonic acid compound is too low, part of sodium carboxymethyl cellulose will not be modified; when the amount of sulfonic acid compound is too high, impurities will be introduced.
[0022] In step S2, the reaction time is 3-12 hours.
[0023] The use of the above-mentioned negative electrode dispersant for lithium-ion batteries or the negative electrode dispersant for lithium-ion batteries prepared by the above-mentioned method in the preparation of battery pole pieces also falls within the protection scope of the present invention.
[0024] The use of the lithium ion battery negative electrode dispersant or the lithium ion battery negative electrode dispersant prepared by the above method in lithium ion batteries also falls within the protection scope of the present invention.
[0025] The negative electrode material is a combination of one or more of graphite (including natural graphite and artificial graphite), hard carbon, silicon-carbon composite material, tin, tin oxide, tin nitride, niobium pentoxide, etc.; the carbon black conductive agent includes a combination of one or more of acetylene black, 350G, carbon fiber (VGCF), carbon nanotubes (CNTs), Ketjenblack (KetjenblackEC300J, KetjenblackEC600JD, CarbonECP, Carbon ECP600JD), etc.; the binder is one or a combination of two of styrene-butadiene rubber (SBR) and polyacrylic acid (PAA).
[0026] The lithium ions in the electrolyte of the present invention are driven to the lithium-philic functional sites on the surface of the negative electrode skeleton through the potential gradient, the lithium ion concentration gradient and the electrostatic interaction between the lithium ions and the electronegative sites in the skeleton. Increasing the lithium-philic sites in the negative electrode can accelerate the migration rate of lithium ions at the solid-liquid interface and inside the electrode sheet, promote the kinetic process of the electrochemical reaction, and improve the rate performance of the battery. The present invention prepares a material with the function of accelerating lithium ion conduction by grafting a functional group with a large electronegativity on the negative electrode auxiliary material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The grafting of organic sulfonates accelerates the migration rate of lithium ions in the electrochemical reaction, promotes the kinetic process of the electrochemical reaction, and improves the rate performance of the battery;
[0029] 2. Sulfonic acid groups serve as efficient lithium-philic functional sites, promoting the uniform distribution of lithium ions at the molecular level of the electrode, thereby achieving rapid and uniform deposition of lithium metal;
[0030] 3. Sulfonic acid group (-SO3H) helps the conduction of lithium ions. By grafting sulfonic acid group, the dispersant sodium carboxymethyl cellulose not only has the function of dispersant, but also accelerates the conduction of lithium ions and increases the reaction kinetics.
[0031] 4. Lithium ions in sulfonates effectively reduce internal resistance, further increase battery specific capacity, greatly improve battery cycle efficiency, and bring a higher charging and discharging platform;
[0032] 5. The increased formation capacity of lithium ions in sulfonates significantly improves lithium precipitation, making lithium-ion batteries safer;
[0033] 6. The lithium ions in sodium carboxymethyl cellulose can supplement lithium, increase lithium ion conduction, and improve battery capacity. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0035] Example 1
[0036] 1) Weigh 20 g of sodium carboxymethyl cellulose powder and dissolve it in 80 mL of hydrochloric acid to precipitate a water-insoluble substance, carboxymethyl cellulose acid. After centrifugation, collect the precipitate, which is carboxymethyl cellulose acid;
[0037] 2) adding a sulfonic acid compound (2 g of lithium aminobenzenesulfonate) and a catalyst (0.1 g of dicyclohexylcarbodiimide (DCC)) to a mixture of a hydrophilic organic solvent (ethanol) and water, wherein the mixture is prepared at a volume ratio of water:ethanol = 1 mL:2 mL;
[0038] 3) adding the carboxymethyl cellulose acid of step 1) to the solution of step S2, heating to 20° C., and reacting (3 h); obtaining sodium carboxymethyl cellulose with grafted functional groups after amide condensation reaction, and baking in an oven at 40° C. for 3 h to obtain modified sodium carboxymethyl cellulose.
[0039] Example 2
[0040] 1) Weigh 20 g of sodium carboxymethyl cellulose powder and dissolve it in 80 mL of hydrochloric acid to precipitate a water-insoluble substance, carboxymethyl cellulose acid. After centrifugation, collect the precipitate, which is carboxymethyl cellulose acid;
[0041] 2) adding a sulfonic acid compound (4 g of lithium m-aminobenzenesulfonate) and a catalyst (0.5 g of diisopropylcarbodiimide (DIC)) to a mixture of a hydrophilic organic solvent (ethanol) and water, wherein the mixture is prepared at a volume ratio of water:ethanol = 1 mL:4 mL;
[0042] 3) adding the carboxymethyl cellulose acid of step 1) to the solution of step S2, heating to 30° C., and reacting (6 h); obtaining sodium carboxymethyl cellulose with grafted functional groups after amide condensation reaction, and baking in an oven at 70° C. for 2.5 h to obtain modified sodium carboxymethyl cellulose.
[0043] Example 3
[0044] 1) Weigh 20 g of sodium carboxymethyl cellulose powder and dissolve it in 80 mL of hydrochloric acid to precipitate a water-insoluble substance, carboxymethyl cellulose acid. After centrifugation, collect the precipitate, which is carboxymethyl cellulose acid;
[0045] 2) adding a sulfonic acid compound (6 g of lithium 2-amino-3,5-dimethylbenzenesulfonate) and a catalyst (1 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDCI)) to a mixture of a hydrophilic organic solvent (ethanol) and water, wherein the mixture is prepared at a volume ratio of water:ethanol = 1 mL:7 mL;
[0046] 3) adding the carboxymethyl cellulose acid of step 1) to the solution of step S2, heating to 40° C., and reacting (12 h); obtaining sodium carboxymethyl cellulose with grafted functional groups after amide condensation reaction, and baking in an oven at 100° C. for 1 h to obtain modified sodium carboxymethyl cellulose.
[0047] Example 4
[0048] 1) Weigh 20 g of sodium carboxymethyl cellulose powder and dissolve it in 80 mL of hydrochloric acid to precipitate a water-insoluble substance, carboxymethyl cellulose acid. After centrifugation, collect the precipitate, which is carboxymethyl cellulose acid;
[0049] 2) adding a sulfonic acid compound (2 g of lithium aminobenzenesulfonate) and a catalyst (0.1 g of dicyclohexylcarbodiimide (DCC)) to a mixture of a hydrophilic organic solvent (ethanol) and water, wherein the mixture is prepared in a volume ratio of water to ethanol = 1 mL: 9 mL;
[0050] 3) adding the carboxymethyl cellulose acid of step 1) to the solution of step S2, heating to 50° C., and reacting (12 h); obtaining sodium carboxymethyl cellulose with grafted functional groups after amide condensation reaction, and obtaining modified sodium carboxymethyl cellulose after being dried in an oven at 150° C. for 0.5 h.
[0051] Table 1 shows the amount of substances and parameters in the preparation methods of 1-4.
[0052]
[0053] Comparative Example 1
[0054] The difference between this comparative example and Example 1 is that lithium aminobenzenesulfonate is replaced by aniline, and compared with Example 1, the sulfonic acid group is less inserted.
[0055] Comparative Example 2
[0056] The difference between this comparative example and Example 1 is that lithium aminobenzenesulfonate is replaced by ethyl p-aminobenzoate.
[0057] Comparative Example 3
[0058] The difference between this comparative example and Example 1 is that the amount of lithium aminobenzenesulfonate added is 0.5 g.
[0059] Comparative Example 4
[0060] The difference between this comparative example and Example 1 is that the amount of lithium aminobenzenesulfonate added is 10 g.
[0061] Comparative Example 5
[0062] The difference between this comparative example and Example 1 is that unmodified sodium carboxymethyl cellulose is used.
[0063] Performance Testing
[0064] The dispersants prepared in the above Examples 1-4 and Comparative Examples 1-5 are used in lithium ion batteries.
[0065] 1. Lithium-ion battery preparation
[0066] Step 1: Preparation of glue. For the positive electrode, N-methylpyrrolidone (NMP) was used as a solvent to prepare a polyvinylidene fluoride (PVDF) glue solution with a solid content of 6%. For the negative electrode, water was used as a solvent to prepare a dispersant glue solution with a solid content of 1.5%.
[0067] Step 2: Slurry preparation. Positive electrode: 94.5% LFP + 3.5% Super-P + 2% PVDF, solid content 58% when shipped; Negative electrode: 96.2% graphite + 0.8% Super-P + 1.2% CMC + 1.8% SBR, solid content 52% when shipped.
[0068] Step 3: Coating and rolling. Coat the slurry on the metal foil and evenly coat the prepared positive and negative electrode slurry on the current collector to make a pole piece. The positive current collector uses aluminum foil and the negative electrode uses copper foil. After the pole piece is dried, it is rolled to ensure that the compaction density of the pole piece is consistent.
[0069] Step 4: Cutting and punching. The rolled pole pieces are cut into strips according to the requirements, and then the pole pieces with pole ears are punched out with a mold for later use.
[0070] Step 5: Lamination. The cut electrodes need to be laminated in the order of negative electrode, separator, positive electrode, separator...positive electrode, separator, negative electrode.
[0071] Step 6: Packaging. The stacked cells still need to be welded to the tabs, and the welded cells are placed in the punched aluminum-plastic film and undergo top and side sealing processes.
[0072] Step 7: Injection. Inject electrolyte into the packaged battery cell;
[0073] The electrolyte formula is 26% EC + 25% DMC + 34% EMC + 12.5% LiPF6 + 2.5% VC.
[0074] Step 8: Formation. The battery after injection needs to be charged at a low current, which is equivalent to the activation process of the lithium-ion battery. During the first charging process, a SEI film will form on the surface of the negative electrode. In order to ensure the consistency of battery performance, lithium-ion batteries also need to be tested for capacity division, internal resistance, self-discharge, etc.; first effect = capacity division discharge capacity / formation charging capacity;
[0075] in:
[0076] The chemical process steps are as follows:
[0077] 1) 0.02C current charging to 3.0V cut-off;
[0078] 2) 0.1C current charging to 3.3V cut-off;
[0079] 3) 0.2C current charging to 3.5V cut-off;
[0080] The steps of capacity division are as follows:
[0081] 1) 1 / 3C constant current charging to 3.65V, then constant voltage charging to the current of 0.05C and stop charging;
[0082] 2) 1 / 3C discharge to 2.0V;
[0083] 3) 0.1C discharge to 2.0V;
[0084] 4) 0.05C discharge to 2V.
[0085] 2. Test methods
[0086] At 25℃, first cycle three times with 1 / 3C current, and use the average value of the first three cycles as the initial capacity of the battery. In the fourth cycle, discharge at 1 / 3C for 90 minutes, then discharge at 3C for 30 seconds, and calculate the DCR. Then charge and discharge at 1C, and perform a standard capacity and DCR test every 300 cycles.
[0087] 3. Test results
[0088] The initial gram capacity is measured as shown in Table 2, the first efficiency test is shown in Table 2, and the DCR test after 900 cycles is shown in Table 2.
[0089] Table 2
[0090]
[0091] From the above table, it can be seen that the modified sodium carboxymethyl cellulose (i.e., modified dispersant) prepared in the embodiment of the present invention has greater first-cycle gram capacity and first effect than the modified sodium carboxymethyl cellulose prepared in the comparative example under the same conditions. The modified sodium carboxymethyl cellulose prepared in the embodiment has obvious lithium supplementation effect, and the DCR of the soft-pack battery of the modified CMC is smaller after 900 cycles, which reduces the internal polarization of the battery, improves the sodium carboxymethyl cellulose and has a more obvious lithium ion conduction effect, and reduces the battery energy loss.
[0092] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A lithium ion battery negative electrode dispersant, characterized in that The lithium-ion battery negative electrode dispersant is a modified sodium carboxymethyl cellulose prepared by grafting the carboxyl group on sodium carboxymethyl cellulose and the amino group on the sulfonic acid compound through an amide condensation reaction; The sulfonic acid compound is selected from one of lithium aminobenzenesulfonate, lithium m-aminobenzenesulfonate, and lithium 2-amino-3,5-dimethylbenzenesulfonate; The method for preparing the negative electrode dispersant for lithium ion batteries comprises the following steps: S1, dissolving sodium carboxymethylcellulose powder in a strong acid solution, and obtaining carboxymethylcellulose acid after centrifugation; S2, adding the sulfonic acid compound and the catalyst to a mixture of a hydrophilic organic solvent and water; S3, adding the carboxymethyl cellulose acid of step S1 to the solution of step S2, heating for reaction, and drying the reaction product to obtain modified sodium carboxymethyl cellulose.
2. The negative electrode dispersant for lithium ion batteries according to claim 1, characterized in that: The volume ratio of the water to the hydrophilic organic solvent is 1 mL:2 mL-1 mL:9 mL.
3. The negative electrode dispersant for lithium ion batteries according to claim 1, characterized in that: In step S2, the catalyst is selected from a salt condensation agent or a carbodiimide condensation agent used for amide condensation reaction; The salt condensing agent is selected from one or more of O-(7-azabenzotriazole-1-yl)-bis(dimethylamino)carbonium hexafluorophosphate, O-(benzotriazole-1-yl)-bis(dimethylamino)carbonium hexafluorophosphate, O-(5-chlorobenzotriazole-1-yl)-bis(dimethylamino)carbonium hexafluorophosphate, O-(benzotriazole-1-yl)-bis(dimethylamino)carbonium tetrafluoroborate, O-(N-succinimidyl)-bis(dimethylamino)carbonium tetrafluoroborate, and O-(N-endo-5-norbornene-2,3-dicarbodiimide)-bis(dimethylamino)carbonium tetrafluoroborate; The carbodiimide condensing agent is selected from one or more of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.
4. The negative electrode dispersant for lithium ion batteries according to claim 1, characterized in that: In terms of weight, the weight ratio of sodium carboxymethyl cellulose powder, sulfonic acid compound and catalyst is 100 parts: 10-30 parts: 0.1-5 parts.
5. The negative electrode dispersant for lithium ion batteries according to claim 1, characterized in that: In step S3, the reaction time is 3-12 hours.
6. Use of the negative electrode dispersant for lithium ion batteries as claimed in any one of claims 1 to 5 in the preparation of battery pole pieces.
7. Use of the negative electrode dispersant for lithium ion batteries as claimed in any one of claims 1 to 5 in lithium ion batteries.
Citation Information
Patent Citations
Negative electrode dispersing agent and lithium ion battery containing dispersing agent
CN113045777A
Lithium ion battery, negative electrode pole piece and preparation method of lithium ion battery
CN103855360A
Aqueous adhesive for lithium ion battery, and preparation method and use thereof
CN106207184A
Method for producing amide-modified carboxymethylcellulose
JP2009114437A